Survival Patterns in United States (US) Medicare Enrollees with Non-CML Myeloproliferative Neoplasms (MPN) - Price, Gregory L.; Davis, Keith L.; Karve, Sudeep; Pohl, Gerhardt; Walgren, Richard A. (PloS one, 2014)
Non-CML myeloproliferative neoplasms (MPN) include essential thrombocythemia (ET), polycythemia vera (PV), and myelofibrosis (MF). Reported median overall survival (OS) ranges from a few to several years for MF, a decade or more for ET and PV. The study objective was to compare US survival rates of ET, PV, and MF patients with matched non-MPN/non-cancer controls in a nationally representative database. Data were taken retrospectively from the Survey, Epidemiology, and End Results (SEER)-Medicare linked database. Medicare enrollees with a new SEER MPN diagnosis between Jan 1, 2001 and Dec 31, 2007 were eligible. First MPN diagnosis was required at or after Medicare enrollment to allow for continuous follow-up. Non-MPN/non-cancer control groups were selected from Medicare separately for each MPN subtype and demographically matched to cases at a ratio of 5:1. Survival was determined starting from the case diagnosis date using the Kaplan-Meier method. A total of 3,364 MPN patients (n = 1,217 ET; 1,625 PV; 522 MF) met the inclusion criteria and were matched to controls. Mean age was 78.4, 76.1, and 77.4 years for ET, PV, and MF, respectively, and percent female was 63, 50, and 41. Median OS was significantly (p<0.05) lower for MPN cases vs. controls (ET: 68 vs. 101 months; PV: 65 vs. 104; MF: 24 vs. 106). In the US Medicare population, survival in MF patients was worse than that of patients with ET or PV and significantly worse than matched controls. Survival of patients with ET or PV was substantially inferior to matched controls. These findings have implications for the clinical management of MPN patients and underscore the need for effective therapies in all MPN subtypes.